Observation of coherent terahertz edge radiation from compressed electron beams - G. Andonian; A. Cook; M. Dunning; E. Hemsing; G. Marcus; A. Murokh; S. Reiche; D. Schiller; J. B. Rosenzweig; M. Babzien; K. Kusche; V. Yakimenko (Physical Review Special Topics. Accelerators and Beams, 2009)
Coherent radiation emitted from a compressed electron bunch as it traverses the sharp edge regions of a magnetic chicane has been investigated at the Brookhaven National Laboratory Accelerator Test Facility. Electron beam measurements using coherent transition radiation interferometry indicate a 100 fs rms bunch accompanied by distinct distortions in energy spectrum due to strong self-fields. These self-fields are manifested in emitted high power THz radiation, which displays signatures of the phenomenon known as coherent edge radiation. Radiation characterization studies undertaken include spectral analysis, far-field intensity distribution, polarization, and dependence on the electron bunch length. The observed aspects of the beam and radiation allow detailed comparisons with start-to-end simulations.